ARTIFICIAL INTELLIGENCE DALAM DUNIA SEKOLAH: TANTANGAN, PELUANG, DAN PERAN KEPEMIMPINAN PENDIDIKAN - Wahyu Haspri; Indah Susi Irianti; Fathimah , Iim; Sumardjoko , Bambang; Lahir, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to the field of education, particularly in learning processes, school management, and the development of students’ competencies. This article aims to analyze the challenges, opportunities, and the role of educational leadership in addressing the implementation of AI in school environments. The method used in this study is library research by examining various scientific literature, journals, and academic sources related to the use of AI in education. The findings indicate that AI offers substantial opportunities to create more personalized, effective, and data-driven learning experiences. However, the implementation of AI also presents several challenges, including low digital literacy, unequal access to technology, threats to academic ethics, and the readiness of teachers and students to use technology wisely. In this context, educational leadership plays a strategic role in formulating policies, fostering a healthy digital culture, improving educators’ competencies, and ensuring that the use of AI remains aligned with educational and character values. Through adaptive, innovative, and humanistic leadership, schools can utilize AI as a means to improve educational quality without neglecting the moral and social aspects of students.